2019
DOI: 10.3390/ijms20010187
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Implications of Endothelial Nitric Oxide Synthase (eNOS) Function/Dysfunction in Cardiovascular Disease

Abstract: The Global Burden of Disease Study identified cardiovascular risk factors as leading causes of global deaths and life years lost. Endothelial dysfunction represents a pathomechanism that is associated with most of these risk factors and stressors, and represents an early (subclinical) marker/predictor of atherosclerosis. Oxidative stress is a trigger of endothelial dysfunction and it is a hall-mark of cardiovascular diseases and of the risk factors/stressors that are responsible for their initiation. Endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
0
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(173 citation statements)
references
References 271 publications
(362 reference statements)
4
153
0
16
Order By: Relevance
“…Recent evidence suggests that inflammatory factors and oxidative stress play a crucial role in the pathogenesis and progression of AAD [32,33]. For instance, Daiber et al [34] reported the quality of high-density lipoprotein changes under oxidative stress conditions. Similarly, Kaye et al [35] found that if the levels of HDL are insufficient, cholesterol and lipids in arterial walls trigger an exacerbated inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that inflammatory factors and oxidative stress play a crucial role in the pathogenesis and progression of AAD [32,33]. For instance, Daiber et al [34] reported the quality of high-density lipoprotein changes under oxidative stress conditions. Similarly, Kaye et al [35] found that if the levels of HDL are insufficient, cholesterol and lipids in arterial walls trigger an exacerbated inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Taner et al (2013) indicated that serum ADMA may play a role in both the pathophysiology and screening of masked hypertension in diabetic subjects. Accordingly, future therapeutic strategies that could be used to target NOS (Daiber et al, 2019) and/or DDAH (Jarzebska et al, 2019) activity could be promising in the management of cardiovascular and other vascular complications of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…During the acute stages of stroke, ADMA levels are increased by oxidative stress resulting in activation of PRMTs and inhibition of DDAH activity [126,127]. Here, ADMA might be a further generator of oxidative stress via uncoupling of eNOS and iNOS, which leads to synthesis of superoxides [126,128,129]. So far, studies are missing that show ADMA induced uncoupling of NOS in the cerebral circulation.…”
Section: Potential Mechanisms Of Dimethylarginine Response After Ischmentioning
confidence: 99%